1991
DOI: 10.1002/eji.1830210518
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical properties of MHC class II molecules endogenously synthesized and expressed by mouse Langerhans cells

Abstract: The cell surface expression and biosynthesis of Langerhans cells (LC)-derived major histocompatibility complex (MHC) class II molecules from epidermal cells (EC) prepared freshly and cultured for up to 3 days was investigated. Based on the constitutive expression of MHC class II determinants by LC, a panning and magnetic bead selection procedure was employed, yielding 65% and 86% of I-A+ cells, respectively. Phenotypical and cytochemical examinations revealed that the two LC preparations were free of contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 38 publications
(15 reference statements)
3
19
0
Order By: Relevance
“…This is effected by down-regulating the de novo synthesis of MHC class I1 molecules during differentiation from epidermal Langerhans cells, while migrating from the skin to the draining LN. As a result, the MHC class 11-peptide complexes of dendritic cells have a very long half-life, whereas those of MQ turn over and decrease quickly [40,42,431. In this way, dendritic cells may be very efficient in the continued presentation of Ag from dormant intracellular pathogens, or from degraded organisms, and may be responsible for the maintenance of T cell memory.…”
Section: Discussionmentioning
confidence: 99%
“…This is effected by down-regulating the de novo synthesis of MHC class I1 molecules during differentiation from epidermal Langerhans cells, while migrating from the skin to the draining LN. As a result, the MHC class 11-peptide complexes of dendritic cells have a very long half-life, whereas those of MQ turn over and decrease quickly [40,42,431. In this way, dendritic cells may be very efficient in the continued presentation of Ag from dormant intracellular pathogens, or from degraded organisms, and may be responsible for the maintenance of T cell memory.…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal cell (EC) suspensions were prepared according to Becker et al [17] with modifications using whole pelts. Briefly, the pelts were cut into strips, and treated with 70% isopropanol for 5 s. After rinsing with cold phosphate buffered saline (PBS) strips were incubated in PBS supplemented with 0.5% (w/v) dispase type II (Boehringer-Mannheim, Mannheim, Germany) at 4ЊC overnight.…”
Section: Methodsmentioning
confidence: 99%
“…For an effective generation of a ligand for the antigen-specific T cell receptor (i. e., immunogenic MHC class II/peptide complex) by the antigen-presenting cell, it is necessary that MHC class II molecules and associated invariant chain molecules be available. Biochemical analysis of MHC class II molecules and associated invariant chains in LC showed that freshly isolated LC synthesize large amounts of these molecules [3,27,43]. In parallel with the decline in processing function the synthesis of both molecules was shut down.…”
Section: Sentinel Function Of Dendritic Cells/langerhans Cellsmentioning
confidence: 97%